PENGARUH EKSPEKTASI PELANGGAN, KUALITAS PRODUK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN INTERNET TELKOMSEL DI BANDA ACEH - Yohandes Rabiqy (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2017)
AbstractThis research aims to examine the factors that influence the level of internet customer loyaltyTelkomsel in Banda Aceh. The population of this research is the customer who use or are subscrib toInternet service Unlimited Telkomsel Flash, and a minimum for six months subscription. Multiplelinear regression analysis is used to determine the effect of variable customer expectations, productquality, and customer satisfaction is hypothesized to effect on customer loyalty. The results of multiplelinear regression analysis showed that the dominant factor that affect the customer loyalty is thevariable quality of the product, followed by a variable customer expectations, and the least effect oncustomer loyalty is customer satisfaction variables. The variables of this research are quite good inexplaining customer loyalty. The advice from the author to the company is that companies have tocreate products that are superior in quality, and always maintain the quality of the product toconstantly innovate on products tailored to the desires of customers to the product. Furthermore, thecompany have to pay attention to the complaints of customers by minimizing customer complaints.Keywords: Expectations, product quality, customer satisfaction, customer loyalty